Dynamic-Static Var Compensation for Improving Power Factor - Basnet, Biswash; Sapkota, Kishor; Poudel, Rabison; Kshetri, Sandip; Pandey, Ram Prasad (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.